1989
DOI: 10.1099/00221287-135-7-2093
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Staphylococcal Species and Strains by Ribosomal RNA Gene Restriction Patterns

Abstract: Staphylococcal DNA was digested with endonucleases and probed with labelled ribosomal RNA (rRNA) from Escherichia coli. Reproducible restriction patterns containing between seven and 22 bands were obtained for seven different species of staphylococci. These profiles were species-specific with different strains of a particular species sharing an identical or similar restriction pattern. The results reported here indicate that rRNA gene restriction pattern analyses have an application in the taxonomy of staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 14 publications
8
49
0
Order By: Relevance
“…In our study, the rDNA fingerprinting technique, which has been applied in recent years to many bacterial species [7][8][9][10], was used on strains of S. typhimurium isolated over the last 10 years in Italy from human and non-human sources, in order to investigate the epidemiological features of interchange of clones between man and animal hosts.…”
Section: Introd)uctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the rDNA fingerprinting technique, which has been applied in recent years to many bacterial species [7][8][9][10], was used on strains of S. typhimurium isolated over the last 10 years in Italy from human and non-human sources, in order to investigate the epidemiological features of interchange of clones between man and animal hosts.…”
Section: Introd)uctionmentioning
confidence: 99%
“…In our study, the rDNA fingerprinting technique, which has been applied in recent years to many bacterial species [7][8][9][10], was used on strains of S. typhimurium isolated over the last 10 [7,11,12]. The hybridized bands were visualized by the 'Blugene' non-radioactive nucleic acid detection system (Gibco-BRL.…”
Section: Introd)uctionmentioning
confidence: 99%
“…Many other techniques have been used to investigate isolates of S. aureus, such as peptidoglycan f i n g e~r i n t i n g ,~~ immunoblotting of exported proteins and restriction enzyme fragmentation patterns,26 penicillin-binding protein analysis2' and ribotyping. 28 Further work is required to assess the suitability of these techniques for CNS. Most recently the typing of CNS by pyrolysis mass spectrometry has shown promise.29…”
Section: Discussionmentioning
confidence: 99%
“…Studies on a variety of micro-organisms including Haemophilus infiuenzae (Irino et al 1988), Staphylococcus spp. (De Buyser et al 1989;Thomson-Carter et al 1989) and Streptococcus thermophilus (Salzano et al 1994) have demonstrated that rRNA gene restriction pattern analysis provides a means of distinguishing between strains at species, subspecies or other taxonomic levels. The study of polymorphism of ribosomal DNA, facilitated by restriction analysis of rRNA genes amplified by polymerase chain reaction (ARDRA-PCR), has also been used for the differentiation of species and subspecies (Gurtler et al 1991;Jayarao et ul.…”
Section: Introductionmentioning
confidence: 99%